Two novel bipolar Ir(III) complexes based on 9-(4-(pyridin-2-yl)phenyl)-9H-carbazole and N-heterocyclic ligand. (November 2017) - Huixia, Xu; Fang, Wang; Kexiang, Wang; Peng, Sun; Jie, Li; Tingting, Yang; Hua, Wang; Bingshe, Xu
Abstract: Two novel bipolar Ir(III) complexes named(Czppy) 2 Ir(tfmptz) and(Czppy) 2 Ir(pptz) were synthesized and characterized, where the Czppy is 9-(4-(pyridin-2-yl)phenyl)-9H-carbazole, tfmptz refers to 2-(3-(trifluoromethyl)-1H-1, 2, 4-triazol-5-yl)pyridine andHpptz represents 2-(1H-tetrazol-5-yl)pyridine, respectively. Their molecular structures were confirmed by 1 H NMR and photophysical were investigated. The performances in phosphorescent organic light emitting devices (PhOLEDs) were characterized by a heavy doping concentration of 20 wt% in host as emitting layer. The results suggest that the number of nitrogen atoms in ancillary has no obvious effects on their photophysical properties. Both(Czppy) 2 Ir(tfmptz) and(Czppy) 2 Ir(pptz) display the blue-green emission with the peaks at 492, 526 nm. The performances of complexes(Czppy) 2 Ir(tfmptz) in PhOLEDs superior to that of the(Czppy) 2 Ir(pptz) due to the poor thermal stability. Graphical abstract: Highlights: The bipolar Ir(III) complexes were designed and synthesized. The green-blue emission was observed. The performances in PhOLEDs were characterized by the heavy dope concentration.